PENGARUH CURRENT RATIO DAN DEBT TO ASSET RATIO TERHADAP RETURN ON ASSET PADA PT ASTRA INTERNASIONAL TBK PERIODE 2008-2022 - Primatama, Harley; Nuryani, Yusni (Journal of Research and Publication Innovation, 2024)
This study aims to determine whether Current Ratio (CR) and Debt to Assets Ratio (DAR) have an effect on Return on Assets (ROA) at Pt Astra International. Tbk for the 2008–2022 period. This research uses a descriptive method with a quantitative approach. The population used in this research is the financial report of Pt Astra International, Tbk while the sample used is the profit and loss report and balance sheet at Pt Astra International, Tbk for the period 2008–2022. The data analysis method uses descriptive statistical analysis tests, classical assumption tests, multiple linear regression tests, coefficient of determination tests, and hypothesis tests with the help of the SPSS version 26 program. The results of this study indicate that Current Ratio (CR) has no partial and significant effect on Return on Asset (ROA). Debt to Assets Ratio (DAR) has no partial and significant effect on Return on Asset (ROA). Current Ratio (CR) and Debt to Assets Ratio (DAR) not simultaneously and significantly affect Return on Asset (ROA). The coefficient of determination is -0,047 or 0%. This means that the variables Current Ratio (CR) and Debt to Assets Ratio (DAR) have an influence contribution of 0% to Return on Assets (ROA), while the rest 100% is influenced by other factors not examined.